Epilogue - Verena Balz (A+BE: Architecture and the Built Environment)
This dissertation investigated regional-design practices that evolved in the context of Dutch national planning frameworks in the period between the 1980s and the 2010s. Questions concerned whether and how practices influenced these planning frameworks, and the extent to which practices were influenced by shifts that frameworks underwent over time. The main aim of the dissertation was to develop an enhanced understanding of interrelations between regional design and spatial planning, so the performances of regional design in the spatial-planning realm can be better anticipated.